Sigmoido-vesical fistula secondary to hernia mesh migration; a long-term rare complication of laparoscopic transabdominal preperitoneal inguinal hernia repair - Mehta, Anuj; Kandoi, Nilay; Godhani, Meet; Reddy, Kotha Nikhil; Patel, Vishva (International Surgery Journal, 2023)
A 47-year old male presented with frequent urinary tract infections (UTIs), hematuria and pneumaturia with a past history of laparoscopic bilateral inguinal hernia repair 5 years ago. Ultrasonography (USG) and contrast enhanced computed tomography did not furnish any evidence to arrive at a diagnosis, interestingly, cystoscopy revealed a mesh in the urinary bladder making apparent the diagnosis of Sigmoido-vesical fistula secondary to mesh migration. Later, surgical removal of the mesh from the sigmoid colon and urinary bladder with rent closure of the fistulous opening was done successfully. Our case thus, highlights the long-term rare complication of transabdominal preperitoneal (TAPP) surgery.